Investigating the Cases of Pupillary Paraffinoma Following Surgery on the Paranasal Sinus Surgeries: Case Series - Behzad Khademi; Naser Owji; Elham Sadeghi; Zahra Zia; Fatemeh Ebrahimi; Ali Azimi; Mohammad Hassan Jalalpour; Reza Jahangir (مجله علوم پزشکی صدرا)
Introduction: In medicine, paraffinoma is a rare and intriguing condition. This condition is characterized by an orbital lipogranulomatosis reaction caused by the penetration of mineral oils (especially paraffin) into the tissues surrounding the eye.Patients’ Presentation: This case series reported three cases of orbital paraffinoma. All cases were occurred following endoscopic paranasal sinus surgery. Consequently, a literature review was conducted on orbital and peri-ocular paraffinoma. The disease-related data were classified into disease definition, differential diagnosis, clinical manifestation, radiological manifestation, histopathological diagnosis, and treatment methods, which were comprehensively reviewed.Conclusion: Paraffinoma is a rare and time-delayed diagnosis following various peri-orbital surgeries, which might challenge the physician to make an accurate diagnosis at first. When patients with a history of sinus and nose surgery have masses around their orbit and eyelids, ophthalmologists should take this diagnosis into account in addition to other differential diagnoses. Therefore, otolaryngologists and ophthalmologists should prioritize prompt prevention and timely management.